Analysis of relapse-free and overall survival in oncoplastic and organ-preserving surgeries in patients with breast cancer - O. G. Babayeva; S. V. Sidorov; S. S. Novikov; T. E. Kvon; K. E. Shevchenko (Исследования и практика в медицине, 2021)
Purpose of the study. To study the results of relapse-free and overall survival during organ- preserving and oncoplastic surgeries in patients with breast cancer.Materials and methods. A prospective clinical study of 84 patients was carried out in the mammology department on the basis of GBUZ NSO "GKB № 1". The first group of patients (40 patients) underwent OPR with ALAE - oncoplastic resection of the mammary gland with axillary lymphadenectomy. The second group (44 patients) WSR with ALAE - wide sector resection of the mammary gland with axillary lymphadenectomy.During the study, the patients were comparable in age, stage (TNM), histological type, and morphogenetic data. The survival rate was studied by the number of local relapses and distant metastases, using laboratory and instrumental studies. The quality of life was assessed on the basis of anamnestic data (Karnofsky index, ECOG scale).Results. In the first group of patients, disease-free and overall survival rate was 97.5 %. At the same time, a local recurrence was found in a patient with a triple negative tumor type, distant metastases to the lungs in a patient with a HER2/neu-positive type. In the second group, relapse-free survival was 95.4 %, overall - 97.7 %. Relapses in two patients with HER2/neu-positive type, metastases to the lungs in a patient with triple negative type.Conclusion. Relapse-free survival rates are 2.1 % higher in group I patients who underwent oncoplastic resection with axillary lymphadenectomy. And the indicators of overall survival in patients of both groups do not differ relatively.